Effect of oral antiseptics in reducing SARS-CoV-2 infectivity: evidence from a randomized double-blind clinical trial. Issue 1 (31st December 2022) - Sánchez Barrueco, Álvaro; Mateos-Moreno, María Victoria; Martínez-Beneyto, Yolanda; García-Vázquez, Elisa; Campos González, Alfonso; Zapardiel Ferrero, Javier; Bogoya Castaño, Abel; Alcalá Rueda, Ignacio; Villacampa Aubá, José Miguel; Cenjor Español, Carlos; Moreno-Parrado, Laura; Ausina-Márquez, Verónica; et al.
ABSTRACT : Background: In vitro studies have shown that several oral antiseptics have virucidal activity against SARS-CoV-2. Thus, mouthwashes have been proposed as an easy to implement strategy to reduce viral transmission. However, there are no data measuring SARS-CoV-2 viability after mouthwashes in vivo . Methods: In this randomized double-blind, five-parallel-group, placebo-controlled clinical trial, SARS-CoV-2 salivary viral load (by quantitative PCR) and its infectious capacity (incubating saliva in cell cultures) have been evaluated before and after four different antiseptic mouthwashes and placebo in 54 COVID-19 patients. Results: Contrary to in vitro evidence, salivary viral load was not affected by any of the four tested mouthwashes. Viral culture indicated that cetylpyridinium chloride (CPC) significantly reduced viral infectivity, but only at 1-hour post-mouthwash. Conclusion: These results indicate that some of the mouthwashes currently used to reduce viral infectivity are not efficient in vivo and, furthermore, that this effect is not immediate, generating a false sense of security. Trial registration: ClinicalTrials.gov identifier: NCT04707742. .